2011
DOI: 10.1007/s12032-011-9938-4
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib-based chemotherapy for light chain deposition disease presenting as acute renal failure

Abstract: We report a case of kappa light chain deposition disease (LCDD) associated with multiple myeloma in a patient presenting with acute renal failure, 2+ proteinuria and hypercalcemia. Serum protein electrophoresis showed an M-spike at 0.1 g/dL. 24-h urine protein electrophoresis showed Bence-Jones proteinuria of 3.8 g. Serum-free light chain assay found excess kappa chains at 3080 mg/L, with normal lambda and an elevated kappa:lambda ratio of 124.7. A kidney biopsy revealed kappa light chain nephropathy with PAS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 14 publications
3
16
0
Order By: Relevance
“…Excretion of hydrogen ion and potassium will be impaired if the light chain deposits involves the tubules (17). Kidney function prognosis in MM patients with LCDD is dismal despite reports showing a reduction of proteinuria and stabilization of renal function in several uncontrolled studies and case reports (18)(19)(20). Most such cases end up rapidly developing end-stage renal disease (ESRD).…”
Section: Discussionmentioning
confidence: 99%
“…Excretion of hydrogen ion and potassium will be impaired if the light chain deposits involves the tubules (17). Kidney function prognosis in MM patients with LCDD is dismal despite reports showing a reduction of proteinuria and stabilization of renal function in several uncontrolled studies and case reports (18)(19)(20). Most such cases end up rapidly developing end-stage renal disease (ESRD).…”
Section: Discussionmentioning
confidence: 99%
“…Bortezomib has been suggested to inhibit NF-κB, thereby decreasing TGF-β levels and collagen production, eventually preventing glomerulosclerosis and renal dysfunction (11)(12)(13). Furthermore, several case reports have already shown that bortezomib stabilizes the renal function in patients with LCDD without serious adverse effects (19)(20)(21)(22)(23)(24). Based on these data and those obtained from reports, it was decided to administer BD therapy to this elderly patient.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been reported among LCDD patients. Table shows a list of previous reports describing patients with LCDD who received bortezomib-based regimens without high-dose chemotherapy (11,14,15). The patient described here showed an abrupt elevation in the serum levels of hepatobiliary enzymes after the first cycle of the VCD regimen.…”
mentioning
confidence: 86%